Competencies of pre-service mathematics teachers when transforming the representations of a function - Amaya De Armas, Tulio (2021)
This paper aimed to analyze the competencies of pre-service secondary school mathematics teachers when transforming the representations of a function. The information was collected during the second half of 2019 and was processed using the content analysis technique. For this qualitative study, researchers interacted with pre-service teachers while they solved problems involving functions and prepared a class that they later simulated before their professor and classmates. The sample included 36 students from the Mathematics Education Program of a Chilean university. Results show that pre-service teachers were able to produce multiple ways of representations of the analyzed functional relationships, which facilitated the analysis and establishment of connections with sociocultural elements.  However, some participants faced difficulties with perceptual fluency, which prevented them from establishing connections. The partial meanings of the functions were articulately modified until they became one, in which time multiple representations were produced and articulated. In conclusion, interventional processes should be implemented to help future teachers make more comprehensive analyzes of functions and have an operational use of their knowledge, in order to minimize learning difficulties in students.